SEMANTIC CONCORDANCE IN THE SUPPLICATIONS OF SHEMISBAH IKH AL-TUSI IN THE BOOK OF AL-MUTAHJID (AN ANALYTICAL STUDY) - Hassan Farouk Noman AL-Tawaijiri, Dr. Hussein Nazare (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In this study, we dealt with the phenomenon of semantic contrast in the book of Misbah Al-Mutahjid to Al-Tusi, and it tries to answer the following questions: Does the semantic encounter exist in the Arabic language, the Holy Qur’an, and the book of Misbah al-Mutahjid ? And what is the opinion of scholars about its occurrence in the Noble Qur’an? One of its importance is to shed light on the issue of semantic contrast in the book of Misbah Al-Mutahjid to Al-Tusi with clarifying the views of scholars on this phenomenon, and the study aims to mention scholars' opinions about its different naming, and it included three topics, the first topic was entitled: Definition of semantic contrast in language and idiom, and the second topic Its title: The role of encounter to produce significance in the Noble Qur’an. As for the third topic, it was titled the semantic contrast in the supplications of Sheikh al-Tusi in the book of Misbah al-Mutahjid. The study also included findings and recommendations, and among the most important results: The semantic contrast is present in the Arabic language, the Holy Qur’an, and the book of Misbah al-Mutahjid al-Tusi The title of my article for his study was semantic, especially the semantic encounter of it. The scholars paid attention to and devoted many books to, it and what the study recommended: the need to pay attention to semantic contrast by researchers, and to make special books about it.